Automated Indexing Based on SNOMED - Wingert, F. (Methods of Information in Medicine, 1985)
Structure and content of SNOMED are described with special consideration of the German edition. An introduction into the problems of automated indexing and the related structural elements of SNOMED is given because they are the basis of algorithms for automated indexing to be published in subsequent papers.
Keywords: SNOMED; Automated Indexing; Nomenclatures